2012
DOI: 10.1002/jcp.23024
|View full text |Cite
|
Sign up to set email alerts
|

Activity of matrix metallo proteinases (MMPs) and the tissue inhibitor of MMP (TIMP)‐1 in electromagnetic field‐exposed THP‐1 cells

Abstract: Matrix metalloproteinases (MMPs) and tissue inhibitors of MMPs (TIMPs) are the main determinants of tissue remodeling in both physiological and pathological processes. Metabolic processes, which generate oxidants and antioxidants can be influenced by environmental factors such as electromagnetic fields (EMF). We analyzed the effects of EMF on the activity and expression of MMPs in THP-1 cells. Cells were exposed to a 50 Hz, 1 mT EMF for 24 h and incubated with or without LPS. Our data indicate that THP-1 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 48 publications
3
40
0
Order By: Relevance
“…It is well known that the activities of MMPs are regulated by TIMPs through their NH 2 -terminal inhibitory domain (34,39,48,50,52). Hence the levels of TIMPs were determined in lungs of SIRT1 ϩ/Ϫ and SIRT1 Tg mice as well as WT littermates in response to CS exposure.…”
Section: Overexpression Of Sirt1 Decreases the Protein Level And Actimentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the activities of MMPs are regulated by TIMPs through their NH 2 -terminal inhibitory domain (34,39,48,50,52). Hence the levels of TIMPs were determined in lungs of SIRT1 ϩ/Ϫ and SIRT1 Tg mice as well as WT littermates in response to CS exposure.…”
Section: Overexpression Of Sirt1 Decreases the Protein Level And Actimentioning
confidence: 99%
“…Genetic overexpression of MMP-9 causes air space enlargement, whereas deficiency of MMP-12 attenuates cigarette smoke (CS)-induced pulmonary emphysema in mice (14,16). It has been shown that TIMPs are subjected to posttranslational modifications, such as acetylation, oxidation, and nitration, thereby regulating their ability to inhibit MMPs (34,39,48,50,52). However, it is unknown whether TIMPs undergo these posttranslational modifications, particularly in response to CS leading to upregulation of MMPs, and whether SIRT1 has a regulatory role in redressing the TIMP/MMP imbalance.…”
mentioning
confidence: 99%
“…In the EL-EMF exposure group, MMP-2 expression increased. Other studies showed that an increasing MMP-2 gene expression took place when SK-OV-3 ovarian cancer cells were exposed to EL-EMF (Patruno et al 2012). But these two factors act together to reduce the expression of these genes.…”
Section: Semi-quantitative Rt-pcr Resultsmentioning
confidence: 95%
“…MMPs are enzymes that are essential for this process. MMPs play a role in the degradation of the extracellular matrix by promoting epithelial-mesenchymal transition, promoting the activation of growth factors, their receptors and angiogenesis, and facilitating tumor invasion and metastasis (24)(25)(26)(27). Previous studies revealed that the expression of MMP-2 in breast cancer tissue is higher compared with normal breast tissue.…”
Section: Discussionmentioning
confidence: 99%